EFEK PENGHAMBATAN EKSTRAK N-HEKSANA BUAH MENGKUDU (Morinda citrifolia L.) TERHADAP REAKSI ANAFILAKSIS KUTANEUS AKTIF PADA TIKUS WISTAR YANG DIINDUKSI VAKSIN HEPATITIS B - Ediati Sasmito; Agung Endro Nugroho; Yose V. Sagala (Faculty of Pharmacy, Universitas Gadjah Mada, 2014)
Noni (Morinda citrifolia L.) is one of medicinal plants that are commonly known for its medical treatment usage. Noni is reported for the pharmacological effects, including analgesic, antihypertensive and immunomodulator. This research aims to prove that the n-hexane extract of noni fruits can inhibit active cutaneous anaphylaxis reaction in male wistar rats induced hepatitis B vaccine. This research used an active cutaneous anaphylaxis methode followed by hystopathological observation. Active cutaneous anaphylaxis test was done for 2 weeks. Test animals were divided into five groups: untreated control, treatment with n-hexane extract of noni dose of 50mg, 100mg dan 200mg/kgBW rats, and cromolyn treated group with dose of 2. mg/kg BW rats as positive control. Animals were sensitized 2times (once every week) with hepatitis B vaccine (dose of 145µg/kgBW) subcutaneously on the back. In the second week, random four rats of each groups were sacrificed and the skin tissues and livers were taken. Tissues were created as histopathology preparations with hematoxyllin-eosin coloring. The presence of anaphylaxis reactions, shown by inflammatory cell infiltration, were observed from the histopathology preparations. The result of this research showed that the administration of n-hexane extract of noni fruits treatment dose of 50mg, 100mg, and 200mg/kgBW on male Wistar rats induced hepatitis B vaccine can inhibit active cutaneous anaphylaxis reaction.